Use Of Promoter-Anchored Rapd Analysis For Divergence Assessment In Soybean As Against Conventionally Used Issr Assay (Applied Biological Research, 2017)
The present study was aimed to compare the genetic diversity among 24  soybean genotypes as revealed by Promoter-anchored amplified  polymorphism based on RAPD (PAAP-RAPD) primer-combinations  analysis and Inter Simple Sequence Repeat (ISSR) analysis. All the 16  PAAP-RAPD primer-combinations, derived from 4 Promoter-based  primers (TA1/G1/CA1/GC1) and 4 RAPD primers (OPE 1/5/7/9) showed  amplification, of which 8 were polymorphic. They produced 63 loci, of  which 52 were polymorphic. All 20 ISSR primers used were polymorphic  generating 115 alleles of which 95 were polymorphic. The similarity  coefficient based on ISSR and PAAP-RAPD analysis ranged from 0.67 to  0.93 and 0.41 to 1.00, respectively. The PAAP-RAPD consensus tree  revealed 17 clusters; while ISSR revealed all genotypes as separate  clusters. In 2D scatter plot, these were broadly classified into 5 major  groups. Group-Ia had lowest divergence (MAUS71, KDS 344, KDS387,  NRC94, KDS722, Bragg and KDS743) while Group-Ib had low divergence  (Birsa Soya1, KDS749, KDS726, KDS739 and JS335). Moderate  divergence was observed in Group II (JS9305 and RKS 18) and Group III  (Himso 1684, Dsb22 and MACS450). Group IV (KDS741, VLS65, Rpp3  PI462312 variant, EC241778 and PI462312) had highest divergence. Only  two genotypes (KDS753 and DS228) were placed separately in both the  analyses. The study revealed that PAAP-RAPD has an advantage that it  may specifically target regulatory regions of various candidate genes  during molecular tagging for a specific trait.
Keywords: Diversity; ISSR; PAAP-RAPD markers; soybean